Implementation of Fraud Risk Management to Minimize Fraud Risk in Wanda Putra Kencana Surabaya - Rosliana Rosliana; Elliany Elliany; Wiwin Handayani (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The purpose of this study is to identify the factors that lead to fraud in a commercial entity. The company that manufactures food, is the subject of this study. You will undoubtedly discover fraud done by connected parties when carrying out producing operations until sales. The owners and staff of production, sales, and delivery companies were observed, and interviews with them were conducted as major data sources for this study. This study provides evidence of fraud. The company should take early preventative measures to avoid risks (risks that are not anticipated by the company) from emerging. And with it, perhaps, the use of fraud risk management will help the business reduce current fraud. Implementing fraud risk management involves a number of processes, beginning with an analysis of the internal environment of the corporate organization, followed by the identification of the hazards (risks) that frequently occur so that risk identification and risk mapping may be done. The final point is how to control those risks. Overall, Wanda Putra Kencana's risk management has been fairly effective; the company has implemented physical control, monitoring, and enforcement, as well as rewards and penalties.